Effect of Firm Size, Profitability, and Audit Opinion on Audit Report Lag (in Mining Company Registered in Indonesia’s Stock Exchange for the Financial Year between 2017 and 2020) - Febrianty, Kanita; Raharja, Surya (Diponegoro Journal of Accounting, 2024)
The primary objective of this research is to investigate the impact of three key factors, namely Firm Size, Profitability, and Audit Opinion, on Audit Report Lag. The study focuses on a specific subset of companies, namely those within the mining industry, which were part of the LQ-45 index and listed on the Indonesia Stock Exchange (IDX) during the years 2017 to 2020. To select a representative sample for the analysis, a purposive sampling method was employed, resulting in the inclusion of 31 mining companies in the study. The data used in this research is quantitative in nature and was collected from secondary sources, allowing for a comprehensive examination of the chosen variables. The research methodology encompassed several analytical techniques, including descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, determination of the coefficient of determination (R²), and t-testing. The findings of this study reveal that Firm Size, Profitability, and Audit Opinion had no statistically significant influence on the extent of Audit Report Lag among the selected mining companies. More specifically, the firm size variable yielded a p-value of 0.286, indicating no significant effect. Similarly, the profitability variable showed a p-value of 0.637, indicating no significant impact. Lastly, the audit opinion variable had a p-value of 0.382, suggesting that it also had no significant influence on Audit Report Lag. This study's results indicate that, within the context of mining companies listed on the IDX from 2017 to 2020, Firm Size, Profitability, and Audit Opinion did not appear to be contributing factors to the delay in the issuance of audit reports. These findings offer valuable insights for stakeholders in the mining sector and may have implications for auditing practices within this specific industry.